Application of the Modified Universal Soil Loss Equation (MUSLE) for Soil Erosion Prediction and Erosion Hazard Classification in Nickel Mining - Matilda METBOKI; Chindy Mathelda Sartika FUNAY; Febriani D. TALLO (International Journal of Environmental, Sustainability and Social Science, 2025)
Nickel mining activities in the North Morowali area cause changes in the surface structure of the land and increase the risk of erosion, especially around the settling pond area. The erosion that occurs affects the shallowing of the pond, reduces its sediment storage capacity, and creates a potential for turbid water runoff to overflow into the surrounding environment. This study aims to predict the erosion rate and classify the level of erosion hazard (TBE) using the Modified Universal Soil Loss Equation (MUSLE) method which is more representative of mining conditions with extreme rainfall and dynamic morphology. Data collection was conducted through literature studies, field observations, and the processing of primary and secondary data, including rainfall, soil type, topography, and land use. Data analysis was carried out using ArcGIS 10.8 software for mapping rain catchment areas, slope gradients, and soil classification. The calculation results show that the annual sedimentation rate reaches 7256.073 m³/year, with a sedimentation rate of 62.806 tons/ha/year, and is included in the class III category (moderate erosion). Conservation recommendations are directed at a combination of vegetative methods, such as planting cover crops and local vegetation, and mechanical methods such as terracing and drainage channels according to slope contours.